2017
DOI: 10.1038/s41598-017-09037-z
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin K knockout protects against cardiac dysfunction in diabetic mice

Abstract: Diabetes is a major risk factor for cardiovascular disease and the lysosomal cysteine protease cathepsin K plays a critical role in cardiac pathophysiology. To expand upon our previous findings, we tested the hypothesis that, knockout of cathepsin K protects against diabetes-associated cardiac anomalies. Wild-type and cathepsin K knockout mice were rendered diabetic by streptozotocin (STZ) injections. Body weight, organ mass, fasting blood glucose, energy expenditure, cardiac geometry and function, cardiac his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 58 publications
5
32
0
Order By: Relevance
“…Here we provide the evidence that cardiomyocyte-specific deletion of Cathepsin K attenuated or ablated doxorubicin-induced aberrant cardiac structure and function, abnormal cardiomyocyte morphology, myofibrillar degeneration, impaired energy metabolism, inflammatory response, and apoptosis. These findings not only support our previous studies that global knockout of Cathepsin K reconciled streptozotocin-, high-fat diet-, and pressure overload-induced cardiac dysfunction 8 , 9 , 11 , but extend these findings to show that the deleterious effects of Cathepsin K in these models are, at least in part, attributable to its cardiac-specific effects. The protective effects of Cathepsin K ablation were associated with alterations in multiple signaling pathways, including restoration of phosphorylation of AMPK, reduction in pro-apoptotic proteins BAX and cleaved-caspase-3, blunted NF-κB signaling, as well as recovery of phosphorylation of AKT.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Here we provide the evidence that cardiomyocyte-specific deletion of Cathepsin K attenuated or ablated doxorubicin-induced aberrant cardiac structure and function, abnormal cardiomyocyte morphology, myofibrillar degeneration, impaired energy metabolism, inflammatory response, and apoptosis. These findings not only support our previous studies that global knockout of Cathepsin K reconciled streptozotocin-, high-fat diet-, and pressure overload-induced cardiac dysfunction 8 , 9 , 11 , but extend these findings to show that the deleterious effects of Cathepsin K in these models are, at least in part, attributable to its cardiac-specific effects. The protective effects of Cathepsin K ablation were associated with alterations in multiple signaling pathways, including restoration of phosphorylation of AMPK, reduction in pro-apoptotic proteins BAX and cleaved-caspase-3, blunted NF-κB signaling, as well as recovery of phosphorylation of AKT.…”
Section: Discussionsupporting
confidence: 88%
“…Elevated levels of Cathepsin K have been demonstrated in both human and animal models of heart failure, atherosclerosis, and coronary heart disease 5 7 . Studies from our laboratory have revealed that global deletion of the Cathepsin K gene protects against cardiac dysfunction associated with pressure overload, diabetes, and aging 8 11 . However, it is unclear whether the beneficial effects of Cathepsin K knockout is attributable to its direct cardiac effects or a secondary effect consequent to improvement in whole-body metabolic changes.…”
Section: Introductionmentioning
confidence: 99%
“…The mice that were bufferinjected showed a higher body weight (30.8 6 0.7 g) throughout the entire experiment, as compared to STZinjected mice (22.7 6 0.5 g) at 24 weeks after diabetes onset. 50 This difference in body weight is consistent with the diabetic phenotype (deterioration of pancreatic b-cell function, coupled to insulin deficiency and systemic hyperglycemia), induced by STZ. STZ-treated mice included in the study, correspondingly showed increased blood glucose levels (477 6 29 mg/dL) as compared to buffer-injected mice (180 6 8 mg/dL) up to the end of the study (Table).…”
Section: Body Weight and Glucose Measurements In Diabetic Micesupporting
confidence: 70%
“…MiR‐185, located in the 22q11.2 gene locus, is generally regarded as a regulator involved in the biological processes of carcinoma cells and neurological disorders by targeting marginal zone B and B1 cell‐specific protein, etc . Several studies have explored the role of CatK in different models of heart failure induced by high‐fat diet, pressure overload, ageing and diabetes . However, the potential mechanisms by which CatK regulates the cardiac function after MI remains unknown.…”
Section: Discussionmentioning
confidence: 99%